The gendered nation : contemporary writings from South Asia - Silva, Neluka (Sage Publications, 2004)
While postcolonial creative writing in English has come of age in South Asia, scholarly examination of this rich body of writing has remained largely confined to the narrow domain of literary criticism. This unusual and well-written book instead foregrounds issues relating to identity, nationalism and gender in contemporary literary writing. To do so, the author has analysed select works which are located within and grapple with four recent periods which have played a significant role in refashioning the nations in the region: the Emergency in India; the ethnic conflict in Sri Lanka; the seces.